2010
DOI: 10.1021/es101559r
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Microbial Generation of Palladium Nanoparticles and Hydrogen To Immobilize Chromate

Abstract: The catalytic properties of various metal nanoparticles have led to their use in environmental remediation. Our aim is to develop and apply an efficient bioremediation method based on in situ biosynthesis of bio-Pd nanoparticles and hydrogen. C. pasteurianum BC1 was used to reduce Pd(II) ions to form Pd nanoparticles (bio-Pd) that primarily precipitated on the cell wall and in the cytoplasm. C. pasteurianum BC1 cells, loaded with bio-Pd nanoparticle in the presence of glucose, were subsequently used to ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 24 publications
3
51
1
Order By: Relevance
“…It has been observed that the microbial activity is helpful to generate an in situ reducing environment for metal ion reduction and the subsequent catalytic reactions as well [60][61][62]. Lenz et al [63] showed the important role of metal species in reduction potential and bacterial uptake efficiency.…”
Section: Au + 8cn + O + 2h O → 4au Cn + 4ohmentioning
confidence: 99%
“…It has been observed that the microbial activity is helpful to generate an in situ reducing environment for metal ion reduction and the subsequent catalytic reactions as well [60][61][62]. Lenz et al [63] showed the important role of metal species in reduction potential and bacterial uptake efficiency.…”
Section: Au + 8cn + O + 2h O → 4au Cn + 4ohmentioning
confidence: 99%
“…All these results proved that the generation of the bioPd(0) was through the reduction of the Pd(II) to Pd(0) on the surface of the K. pneumoniae ECU-15 cells. The location of the bioPd(0) nanoparticles generated might be caused by the distribution and properties of hydrogenase and other enzymes involved in Pd(II) reduction [11]. However, Rotaru found that the cell surface functional groups really played a catalytic function role for the Pd(II) reduction to the bioPd(0) [3].…”
Section: Resultsmentioning
confidence: 99%
“…Many fermentative species could produce hydrogen during fermentation and subsequently reduce Pd(II) to Pd(0). An addition of Pd(II) to the fermenting culture of Clostridium pasteurianum could result in the formation of Pd(0) nanoparticles on the bacterial cell wall and in the cytoplasm [11]. Klebsiella pneumoniae is a potential biohydrogen producer [12] and has the ability to bioreduce Pd(II) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other organisms capable of this metal bioreduction include the Gram-negative bacteria Shewanella oneidensis (De Windt et al 2005), Escherichia coli (Deplanche et al , 2014Mabbett et al 2006), Pseudomonas putida, Cupriavidus necator (Søbjerg et al 2009), Cupriavidus metallidurans , Paracoccus denitrificans , Rhodobacter sphaeroides (Redwood et al 2008), Rhodobacter capsulatus , and the Gram-positive bacteria Bacillus sphaericus (Creamer et al 2007), Arthrobacter oxyidans (Deplanche et al 2014;Wood et al 2010), Micrococcus luteus (Deplanche et al 2014), Staphylococcus sciuri (Søbjerg et al 2009) and Clostridium pasteurianum (Chidambaram et al 2010).…”
Section: Introductionmentioning
confidence: 99%